2021
DOI: 10.1016/j.ajem.2020.08.090
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and quantifying robust risk factors for mortality in critically ill patients with COVID-19 using quantile regression

Abstract: Objective Many laboratory indicators form a skewed distribution with outliers in critically ill patients with COVID-19, for which robust methods are needed to precisely determine and quantify fatality risk factors. Method A total of 192 critically ill patients (142 were discharged and 50 died in the hospital) with COVID-19 were included in the sample. Quantile regression was used to determine discrepant laboratory indexes between survivors and non-survivors and quantile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…From these parameters, pH, P / F ratio, and driving pressure demonstrate increasing importance over the course of IMV. Studies investigating the role of these predictors in critically ill COVID-19 patients are limited, but did identify pH as an important predictor [ 23 ]. No studies are available looking at the role of these predictors throughout the course of ICU admission.…”
Section: Discussionmentioning
confidence: 99%
“…From these parameters, pH, P / F ratio, and driving pressure demonstrate increasing importance over the course of IMV. Studies investigating the role of these predictors in critically ill COVID-19 patients are limited, but did identify pH as an important predictor [ 23 ]. No studies are available looking at the role of these predictors throughout the course of ICU admission.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its relationship with the inflammatory response and severity of COVID-19 manifestations, hypocalcemia has been related to a higher mortality. Several study cohorts demonstrated the relation between lower Ca++ levels at hospital admission and higher risk of in-hospital and 28-day mortality [91,120,121]. Limiting severe acute hypocalcemia could protect from CV and neurological complications that may be fatal.…”
Section: Calciummentioning
confidence: 99%
“…The study by Liu et al [9], in 107 patients, showed that CorrCa levels are associated with a poor outcome evaluated by a composite variable that included the need for mechanical ventilation, ICU admission or death, but they do not provide data on the individual components of the composite variable. Other studies have linked low Ca levels with pro-inflammatory markers, multiple organ injuries and the severity of the disease [10,[27][28][29][30][31].…”
Section: Univariate Analysismentioning
confidence: 99%